2020
DOI: 10.1016/j.nbscr.2020.100059
|View full text |Cite
|
Sign up to set email alerts
|

Poor sleep efficiency and daytime napping are risk factors of depersonalization disorder in female university students

Abstract: Objectives Depersonalization is characterized by feelings of detachment from reality and has been associated with anxiety and depression, both of which have a bi-directional relationship with sleep. To date, few studies have directly examined the potential relationship between sleep and depersonalization, which was the primary objective of our study. Design/methods A cross-sectional study of female, Emirati, university students (n = 100) was conducted. Participants comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…Likewise, the logistic regressions indicated that the presence of depersonalization was associated with high BDI-II scores, which agrees with previous studies indicating a relationship between depersonalization and symptomatology of depression and anxiety ( 41 ). Other studies have also previously related the presence of the symptoms of depression and depersonalization with other components of burnout syndrome such as emotional exhaustion ( 42 ).…”
Section: Discussionsupporting
confidence: 91%
“…Likewise, the logistic regressions indicated that the presence of depersonalization was associated with high BDI-II scores, which agrees with previous studies indicating a relationship between depersonalization and symptomatology of depression and anxiety ( 41 ). Other studies have also previously related the presence of the symptoms of depression and depersonalization with other components of burnout syndrome such as emotional exhaustion ( 42 ).…”
Section: Discussionsupporting
confidence: 91%
“…Dissociative symptoms, particularly depersonalization/derealization, arise when sleep and waking states of consciousness overlap and the boundary between them becomes excessively permeable (Arora et al 2020). When this occurs, dreamlike mentation infiltrates waking life and engenders disturbing experiences of unreality and dream-reality confusion.…”
Section: Dissociation Sleep and Dreamingmentioning
confidence: 99%
“…A study carried out in the United Arab Emirates with university students confirmed the association of depersonalization with poor sleep quality and daytime naps. The authors assert that dissociative experiences are enhanced by sleep quality, especially sleep disorders, due to the difficulty in regulating and controlling the consciousness states that lead to cognitive disinhibition ( 37 ) .…”
Section: Discussionmentioning
confidence: 99%